Populism and Public Administration: Confronting the Administrative State. Issue 10 (November 2019) - Peters, B. Guy; Pierre, Jon
Populism has been perhaps the most popular explanation for the difficulties that have been besetting contemporary governments. But despite the intense interest in populism as a political phenomenon, very little has been written assessing the implications for governance and even less on the implications for public administration. Focusing on the United States, but adding some comparative analysis, this article examines the implications of populist politics for public administration and the role of the bureaucracy in governance.